An enhancement of ant colony algorithm applied in automatic exam generation - Cabisora, Angelica B. and Calleja, Isabel D. 4 0 16; 5 (2016)
u
Undergraduate Thesis: (BSCS major in Computer Studies) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2